Analytical Justification of Countering Threats in System Processes - Andrey Kostogryzov (Современные информационные технологии и IT-образование)
Forward-looking systems engineering should be supported by an interdisciplinary theoretical framework, research methods and tools based on models that allow for a better understanding of increasingly complex systems and decisions for countering threats made under the conditions of uncertainty. The purpose of this work is to demonstrate an analytical approach based on the use of risk-oriented methods, models and techniques recommended by the standards of system engineering. The application of the proposed approach, applicable to systems for various purposes, allows for: - predicting the risks associated with the critical entities of the system under consideration, interpretation and analysis of the acceptability of the results obtained, including comparison with acceptable risks; - identification of significant threats and conditions that can negatively affect the quality and/or safety of the system under consideration in one or another development of events in the system life cycle; - definition and justification of proactive measures in the system life cycle to counter threats and conditions that ensure the desired properties of the system quality and/or safety under the consideration of specified restrictions during a specified forecast period. The approach is illustrated by examples.